Research Note: Association of IGF-1R gene polymorphism with egg quality and carcass traits of quail (Coturnix japonica) - Bai, Junyan; Wang, Xinle; Li, Jingyun; Wang, Longwei; Fan, Hongdeng; Chen, Mengke; Zeng, Fanlin; Lu, Xiaoning; He, Yuhan (Poultry science, 2023)
Insulin-like growth factor 1 receptor (IGF-1R) gene is the main effector of insulin-like growth factor (IGF), which plays an important role in growth, development and reproduction of the animal organism. This study aimed to investigate the association of IGF-1R gene single nucleotide polymorphisms (SNPs) with egg quality and carcass traits of quail by direct sequencing. In this study, genomic DNA was extracted from quail blood samples of 46 Chinese yellow (CY) quail, 49 Beijing white (BW) quail and 48 Korean (KO) quail strains. Egg quality and carcass traits were measured and used for IGF-1R gene analysis in 3 quail strains. The results showed that 2 SNPs (A57G and A72T) of the IGF-1R gene were detected in 3 quail strains. The A57G was significantly associated with yolk width (YWI) in BW strain (P < 0.05). Whereas A72T was significantly associated with egg shell thickness (EST) in BW strain (P < 0.05), and significantly associated with egg weight (EW), egg long (EL), and egg short (ES) in KO strain (P < 0.05). Haplotypes based on 2 SNPs showed significant effect on EST in 3 quail strains (P < 0.05), it also has a significant effect on EW in KO strain (P < 0.05). Meanwhile, A72T was significantly associated with liver weight (LW) and dressing percentage (DP) in 3 strains (P < 0.05). Haplotypes showed significant effect on LW (P < 0.05). Therefore, the IGF-1R gene may be a molecular genetic marker to improve egg quality and carcass traits in quails.